Analisis Economic Value Added (EVA) dan Market Value Added (MVA) Sebagai Alat Ukur Kinerja Keuangan Pada Bank Central Asia Tbk Periode 2017-2021 - Muhammad Sirojul Ulum; Kukuh Harianto; Mawar Ratih K (Madani: Jurnal Ilmiah Multidisiplin, 2022)
This research aims to analyze Economic Value Added (EVA) and Market Value Added (MVA) as a tool to measure financial performance at Bank Central Asia Tbk for the 2017-2021 period. Economic Value Added (EVA) can be interpreted as the economic profit value of a company. Market Value Added (MVA) can be called additional market value. This research uses a descriptive research method with a qualitative approach carried out by analyzing financial reports. The type of data used in this research is secondary data in the form of financial reports for 2017-2021. The data collection technique is carried out by accessing the official BCA system and the Indonesian Stock Exchange (BEI) website. For the data analysis technique used, two methods are used, namely Economic Value Added (EVA) and Market Value Added (MVA). Based on the analysis results obtained, PT bank Central Asia Tbk was able to achieve an EVA value> 0 which can be interpreted as PT bank Central Asia Tbk able to generate added economic value in the 2017-2021 period. Then PT bank Central Asia Tbk was also able to achieve an MVA value of> 0, which means that PT bank Central Asia Tbk was able to increase the value of capital invested by funders. These results can be stated that PT bank Central Asia Tbk has good financial performance in the 2017-2021 period.